PRELIMINARY PHYTOCHEMICAL ANALYSIS AND CYTOTOXICITY POTENTIAL OF PINEAPPLE EXTRACT ON ORAL CANCER CELL LINES - Menon, Anirudh; Priya V, Vishnu; R, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study aims at performing a preliminary phytochemical analysis to evaluate the phytochemical composition of pineapple extract and its cytotoxicity potential on oral cancer cell lines. Methods: Preliminary phytochemical analysis of pineapple extract was done, 3-(4, 5-Dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide assay for evaluating the cytotoxicity potential of the extract on oral cancer cell lines was performed. Results: Phytoconstituents such as flavonoids, coumarins, and phenols were present in the pineapple extract. The extract also exhibited increased cytotoxicity with increased concentration. Conclusion: This study is conducted to see if pineapple extract is effective in treating oral cancer in a natural way instead of harmful treatments. Keywords: Cytotoxicity, Pineapple extract, Anticancer drug. Â